The Relationship Between Entrepreneurial Motivation And Entrepreneurial Intensity On Psychology Students - Fatwa Tentama (Universitas Negeri Makassar, 2018)
The purpose of this study is to investigate the relationship between entrepreneurial motivation and the entrepreneurial intention of psychology students. The research subjects were 30 psychology students at Ahmad Dahlan University, in the seventh semester, and have taken entrepreneurial psychology courses. The research subjects were chosen without doing non-randomization (non-randomized) with purposive sampling technique. The data was collected using entrepreneurial motivation and entrepreneurial intention scale. The product moment analysis developed by Pearson was employed. The result of the research shows that the correlation coefficient between entrepreneurial motivation and entrepreneurial intention was = 0,378 with significance level of 0,018 (p <0,05), so it can be concluded that there was a significant positive correlation between entrepreneurial motivation and entrepreneurial intention on students. The higher the entrepreneurial motivation was, the higher the students’ entrepreneurial intention.